The chronic critical illness: a new disease in intensive care (Swiss Medical Weekly, 2016)
Advances in intensive care medicine have created a new disease called the chronic critical illness. While a significant proportion of severely ill patients who twenty years ago would have died survive the acute phase, they remain heavily dependent on intensive care for a prolonged period of time. These patients, who can be called “Patient Long Séjour” in French (PLS) or Prolonged Length of Stay patients in English, develop specific health issues that are still poorly recognised. They require special care, which differs from treatments that are given during the acute phase of their illness. A multidisciplinary team dedicated to ensuring their management and follow-up acquired a wide range of knowledge and expertise about these PLSs. Many new monitoring tools and diverse human approaches were implemented to ensure that care was targeted to these patients’ needs. This multimodal care management aims to optimise the patients’ and their families’ quality of life during and following intensive care, whilst maintaining the motivation of the healthcare team of the unit. The purpose of this article is to present new management techniques to hospital and ambulatory caregivers, physicians and nurses, who may be taking care of such patients.